Family Parenting Counseling in Ranjeng Village, Losarang District, Indramayu Regency - Ismatul Lu'lu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Parenting is a pattern of interaction between parents and children. The pattern of interaction is the way parents behave or behave when interacting with children, including how to apply rules, apply rules, apply values/norms, provide affection and show good attitudes and behavior so that they become role models for their children. The appropriate parenting pattern is one that makes children feel loved, protected, considered valuable, and supported by their parents. Such parenting can form a pro-social, confident and independent personality but very concerned with their environment. The community gives primary authority to parents to meet the needs of their children because parents are considered to know the best things for their children. Parents provide a series of complex needs and qualities in the parenting process. The basic role of parents is to be responsible for parenting. The purpose of this community service is to conduct Family Parenting counseling in Ranjeng Village, Losarang District, Indramayu Regency. The method used is Descriptive Analytical, which is a method that functions to describe or provide an overview of the object being studied through data or samples that have been collected as they are without conducting analysis and making conclusions that apply to the public. The result of this community service is that education for humans is an absolute necessity that must be fulfilled throughout life. Without any education at all, it is impossible for a group of humans to live and develop in line with their ideals to progress, prosper and be happy according to their concept of life.